2002
DOI: 10.1007/s00412-002-0187-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cytogenetic analysis of the telomeric (TTAGGG) n repetitive sequences in the Nile tilapia, Oreochromis niloticus (Teleostei: Cichlidae)

Abstract: The majority of chromosomes in Oreochromis niloticus, as with most fish karyotyped to date, cannot be individually identified owing to their small size. As a first step in establishing a physical map for this important aquaculture species of tilapia we have analyzed the location of the vertebrate telomeric repeat sequence, (TTAGGG)n, in O. niloticus. Southern blot hybridization analysis and a Bal31 sensitivity assay confirm that the vertebrate telomeric repeat is indeed present at O. niloticus chromosomal ends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
45
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 48 publications
5
45
0
Order By: Relevance
“…The length of the telomeric DNA in fish studied to date varies from 2 kb to 15 kb (Chew et al, 2002, Elmore et al 2008 and is similar to that observed in normal human cells (Elmore et al, 2008). Furthermore, retention of the telomere length throughout the entire life has been demonstrated in zebrafish, but not in the medaka (Hatekeyama et al, 2008;Lund et al, 2009).…”
Section: Distribution Of Telomeric Dna Sequences In Fish 41 Telomerasupporting
confidence: 61%
See 2 more Smart Citations
“…The length of the telomeric DNA in fish studied to date varies from 2 kb to 15 kb (Chew et al, 2002, Elmore et al 2008 and is similar to that observed in normal human cells (Elmore et al, 2008). Furthermore, retention of the telomere length throughout the entire life has been demonstrated in zebrafish, but not in the medaka (Hatekeyama et al, 2008;Lund et al, 2009).…”
Section: Distribution Of Telomeric Dna Sequences In Fish 41 Telomerasupporting
confidence: 61%
“…Two interstitial telomeric sites have been detected in the Nile tilapia (Oreochromis niloticus) (2n= 44) chromosome 1 that is significantly larger than all the other chromosomes in this organism (Chew et al 2002). This observation supported hypothesis that chromosome 1 in the Nile tilapia appeared in the course of the fusion of three chromosomes and explained the reduction of chromosome number from the ancestral teleost karyotype of 2n= 48 to 2n= 44 in the Nile tilapia (Chew et al 2002). In Oreochromis karongae, diploid chromosome number is reduced to 38.…”
Section: Fish Karyotype Evolution and Distribution Of Telomeric Repeamentioning
confidence: 97%
See 1 more Smart Citation
“…35 In this species, the first chromosome pair seems to correspond to the sex chromosomes, 41,42 which possibly originated from fusion processes. 43 The determined localization of Rex elements in this chromosome pair could indicate that these TEs might be involved in such chromosome rearrangements. 35 A similar case has also been reported to have occurred with other elements, such as TEs CiLINE2, 36 On2318, 37 and ROn-1, 38,39 which are preferentially situated on the long arm of the largest chromosome pair.…”
mentioning
confidence: 90%
“…The (TTAGGG) n repeat is also found at intrachromosomal sites, including those repeats located close to the centromeres, and at interstitial sites, namely, the sites between the centromeres and telomeres, in which case the repeats are called interstitial telomeric sequences (ITSs) [5][6][7]. ITSs have been described in many species, including fish [8][9][10][11], chicken [12], mouse [13,14], Chinese hamster [15,16], primates [17], Arabidopsis [18] wheat [19], and human [20,21]. ITSs might originate from ancestral intrachromosomal rearrangements (inversions and fusions), from differential crossing-over or from the repair of double-strand break during karyotype and genome evolution [7,20,[22][23][24].…”
mentioning
confidence: 99%